2016
DOI: 10.1111/gwat.12461
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Hydrological Processes in Headwater Riparian Seeps with Time‐Lapse Electrical Resistivity

Abstract: Delineating hydrologic and pedogenic factors influencing groundwater flow in riparian zones is central in understanding pathways of water and nutrient transport. In this study, we combined two-dimensional time-lapse electrical resistivity imaging (ERI) (depth of investigation approximately 2 m) with hydrometric monitoring to examine hydrological processes in the riparian area of FD-36, a small (0.4 km ) agricultural headwater basin in the Valley and Ridge region of east-central Pennsylvania. We selected two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Because a large proportion of nutrients reach the channel through riparian groundwater (Mei et al, 2012), horizontally oriented preferential flow can allow pollutants from upland areas to bypass the beneficial reactions that can occur in riparian soils. Pollutants then emerge in the channel largely undiminished (Flewelling et al, 2012; Williams et al, 2017). For example, riparian preferential flow can contribute more than half the total nitrate load (Bohlke et al, 2007).…”
Section: Preferential Flow In Riparian Zone Groundwatermentioning
confidence: 99%
“…Because a large proportion of nutrients reach the channel through riparian groundwater (Mei et al, 2012), horizontally oriented preferential flow can allow pollutants from upland areas to bypass the beneficial reactions that can occur in riparian soils. Pollutants then emerge in the channel largely undiminished (Flewelling et al, 2012; Williams et al, 2017). For example, riparian preferential flow can contribute more than half the total nitrate load (Bohlke et al, 2007).…”
Section: Preferential Flow In Riparian Zone Groundwatermentioning
confidence: 99%
“…Geophysical imaging can overcome this limitation by providing spatial or volumetric distributions of subsurface physical properties (Binley et al, 2015;Loke et al, 2013). Geoelectrical techniques, which image the electrical resistivity of the subsurface, have been shown to be able to provide reliable, spatial estimates of surface watergroundwater interactions and groundwater flow characteristics, which are in agreement with conventional intrusive investigations (Cardenas and Markowski, 2011;Chambers et al, 2015;Uhlemann et al, 2016;Williams et al, 2016). This is facilitated by the fact that the resistivity of earth materials is not only a function of their lithology, where clay content in particular usually causes a significant resistivity decrease, but also a function of formation water content and pore water conductivity (where increasing water content and/or salinity usually reduces resistivity; Archie (1942)).…”
Section: Introductionmentioning
confidence: 82%
“…Previous research in WE‐38 revealed that nitrate‐N concentrations increase with increasing agricultural land area and decreasing stream order (Kang, Lin, Gburek, Folmar, & Lowery, 2008), groundwater seeps are generally elevated in nitrate‐N concentrations (Pionke et al, 1988), and that the majority (~75%) of nitrate‐N losses in surface water occur during baseflow conditions (Zhu, Schmidt, Buda, Bryant, & Folmar, 2011). Williams et al found that seeps exert strong controls on stream discharge and N chemistry under baseflow conditions and that seep water is mainly sourced from lateral flow in the underlying aquifer that emerges through fractures in the shallow bedrock (Williams et al, 2014, 2016; Williams, Buda, Elliott, Singha, & Hamlett, 2015). Williams et al (2015) also linked seep N concentrations to agricultural practices in upslope recharge areas within the watershed.…”
Section: Methodsmentioning
confidence: 99%